Persepsi Nasabah terhadap Kualitas Layanan dan Partisipasinya pada Program Simpan Pinjam di Koperasi Kuta Mimba - EKASUCI, PUTU AYU WINDA PRASETYANING; ANGGRENI, I GUSTI AYU AGUNG LIES; SUKENDAR, NI MADE CLASSIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Customer Perception of Service Quality and Participation in the Savings and Loan Program at Koperasi Kuta Mimba Kuta Mimba Cooperative is a lending cooperative that has been established since 1983. Lack of customer participation causes cooperatives to conduct evaluations related to service quality and customer participation in the savings and loan program at Koperasi Kuta Mimba. The purpose of this study was to determine customer assessment of the Kuta Mimba Cooperative’s service quality, to determine the level of customer satisfaction with the service quality of Kuta Mimba Cooperative’s employees and to determine customer participation in the savings and loan Kuta Mimba Cooperative’s program. The sample in this study were Kuta Mimba Cooperative’s customers Kuta, Legian and Denpasar branches who were taken using the clutser sampling method with a total of 90 respondents. The data analysis technique used is qualitative analysis with the Likert scale method. From the research results, it can be seen that the quality of employee service and the level of customer satisfaction of the Kuta Mimba Cooperative are good category and customer participation in the savings and loan programs is medium category. Based on the results of this study, it can be suggested that customer participation needs to be increased, especially in the Koperasi Kuta Mimba savings program.